1991
DOI: 10.1364/ao.30.003186
|View full text |Cite
|
Sign up to set email alerts
|

Infrared optical constants and roughness factor functions determination: the HTHRTR method

Abstract: This method was developed to determine the complex infrared optical constant of a single free-standing partially absorbing plate as wellas a thin solid film eposited on it. The method is based on exact formulas for normal transmittance T and near-normal reflectance R of the substrate as well as the film-substrate double layer. Coherent multiple reflections throughout the film and incoherent multiple reflections in the substrate as well as the intensity losses on the rough surface are taken into account. The in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
4
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…The validity of this method has been verified by deriving the optical constants of SiO 2 in the mid-and far-IR regime from the raw transmission data of SiO 2 thin films on SSP Si substrates reported in [9]. The derived absorption coefficient and real part of refractive index using our method are in good agreement with the results in [9].…”
supporting
confidence: 65%
See 2 more Smart Citations
“…The validity of this method has been verified by deriving the optical constants of SiO 2 in the mid-and far-IR regime from the raw transmission data of SiO 2 thin films on SSP Si substrates reported in [9]. The derived absorption coefficient and real part of refractive index using our method are in good agreement with the results in [9].…”
supporting
confidence: 65%
“…The broad oscillations in the wavelength range of 1-5 μm are produced by the multilayer interference effect. Because of the wavelength-dependent scattering caused by the backside roughness of SSP Si and impurity IR absorption in Si [8,9], the transmittance of SSP Si substrates deviates from the theoretical value of ∼55% in the wavelength range of 1.3-22 μm. In particular, the dips in the transmission spectra at ∼9 and ∼16.5 μm correspond to the absorption due to oxygen and carbon in the Si substrate, respectively [10,11].…”
mentioning
confidence: 82%
See 1 more Smart Citation
“…coherent (C)) expression for a thin film on a thick substrate, and then, using heuristic arguments, argued that the derived IC expression becomes exact in the low resolution limit (such as 4 cm −1 ). At roughly the same time, Klansek-Gunde and Alexandrov 26,27 independently utilized the same IC technique to derive analytical expressions for both the transmittance and reflectance of a thin film on thick substrate, and then demonstrated that the two equations could be numerically solved to experimentally extract the optical constants of a thin film. They further extended the IC technique by considering the practical case of surface scattering for single side polished substrates.…”
Section: Overview Of Prior Workmentioning
confidence: 99%
“…Then the reflection and transmission spectra of each sample were recorded using an FTIR (Fourier transform infrared spectroscopy) system. A contour map of reflection and transmission spectra for a range of n and k (real and imaginary parts of the refractive index) was created and overlapped with the experimental results [30,31]. Out of the possible solutions, a meaningful initial estimate was used to choose the correct solution [32].…”
Section: Absorber Designmentioning
confidence: 99%